Ein Labyr ist kein Labyr Carlheinz Casparis Modell ästhetisch-ethischer Selbstbildung zwischen Cage, Constant und den Situationisten - Dörstel, Wilfried 1952- (Kunstwissenschaftliche Bibliothek, 2009)
"Labyr", developed by Carlheinz Caspari in 1960, is an aesthetical-ethical pattern of thought and a cultural technique, which surpasses any previous artistic model in terms of radicalness. This publication is the first examination of "Labyr", analysing it historically as well as through Caspari's texts and correspondences, documented here for the first time.